Triphenylphosphonium Moiety Modulates Proteolytic Stability and Potentiates Neuroprotective Activity of Antioxidant Tetrapeptides in Vitro - Akhmadishina, Rezeda A.; Garifullin, Ruslan; Petrova, Natalia V.; Kamalov, Marat I.; Abdullin, Timur I. (Frontiers in Pharmacology, 2018)
Although delocalized lipophilic cations have been identified as effective cellular and mitochondrial carriers for a range of natural and synthetic drug molecules, little is known about their effects on pharmacological properties of peptides. The effect of triphenylphosphonium (TPP) cation on bioactivity of antioxidant tetrapeptides based on the model opioid YRFK motif was studied. Two tetrapeptide variants with L-arginine (YRFK) and D-arginine (YrFK) were synthesized and coupled with carboxyethyl-TPP (TPP-3) and carboxypentyl-TPP (TPP-6) groups. The TPP moiety noticeably promoted YRFK endopeptidase cleavage by trypsin, but effectively prevented digestion of more resistant YrFK attributed, respectively, to structure-organizing and shielding effects of the TPP cation on stereochemical variants of the tetrapeptide motif. The TPP moiety enhanced radical scavenging activity of the modified YRFK in a model Fenton-like reaction, whereas low reactivity was revealed for YrFK and its TPP derivative. Both the starting motifs and modified oligopeptides, especially the TPP-6 derivatives, suppressed acute oxidative stress in neuronal PC-12 cells during a brief exposure similarly with glutathione (GSH). The effect of oligopeptides was compared upon culturing of PC-12 cells with CoCl2, L-glutamic acid, or menadione to mimic physiologically relevant oxidative states. The cytoprotective activity of oligopeptides significantly depended on the oxidative factor, order of treatment and peptide structure. Pronounced cell-protective effect was established for the TPP-modified oligopeptides, which surpassed that of GSH and the unmodified motifs. The protease-resistant TPP-derivative of YrFK showed the highest activity when administered 24 h prior to the cell damage. Our results suggest that the TPP cation can be used as a modifier for small therapeutic peptides to improve their pharmacokinetic and pharmacological properties.